The war that wasn't : religious conflict and compromise in the common schools of New York State, 1865-1900 - Justice, Benjamin, 1971- (State University of New York Press, 2005)
Historians of religion and public schooling often focus on conflict and Bible Wars, pitting Catholics and Protestants against one another in palpitating narratives of the embattled development of American public schooling. The War That Wasn't tells a different story, arguing that in nineteenth-century New York State a civil system of democratic, local control led to adjustments and compromises far more than discord and bitter conflict.